NATURALLY OCCURRING ANTIOXIDANT VITAMIN LEVELS IN PATIENTS WITH TYPE-II DIABETES MELLITUS - Ahmad, Muhammad; Khan, Mudassir Ahmad; Khan, Abdus Sattar (Journal of Ayub Medical College Abbottabad, 2003)
Background: Type II diabetes mellitus is characterized by an inability of peripheral tissues to respond to insulin and the dysfunction of the endocrine pancreas to compensate for this resistance. Diabetes mellitus is associated with increased lipid peroxidation. Increased levels of lipid peroxides have been implicated in the pathogenesis of diabetic complications. To control and reduce the deleterious effects of lipid peroxides exist several antioxidant protective mechanisms. They comprise of enzymatic defenses and naturally occurring vitamins. The study was designed to determine and compare the antioxidant vitamin levels in Type II diabetic individuals and control healthy subjects. Methods: Blood glucose, triglycerides, total cholesterol, HDL-c, LDL-c, VLDL-c and antioxidant vitamins (Î²-Carotene, A, E, and C) levels were determined in 36 Type II diabetic patients and 30 healthy subjects. Results: Values of blood glucose and lipid parameters were observed to be significantly increased (P< 0.001) with the exception of HDL-c, which was significantly decreased (p<0.001) in Type II diabetes mellitus patients. The levels of antioxidant vitamins (Î²-Carotene, E, and C) were found to be significantly low in Type II diabetes mellitus group whereas the concentration of vitamin A showed a non-significant change when both Type II and control healthy groups were compared. Conclusions: Low levels of antioxidant vitamins observed in the study suggest, that Type II diabetes mellitus patients have significant defects of antioxidant protection.